2017
DOI: 10.1038/srep45111
|View full text |Cite|
|
Sign up to set email alerts
|

Compatibility Study of Danggui Buxue Tang on Chemical Ingredients, Angiogenesis and Endothelial Function

Abstract: Danggui Buxue Tang (DBT) is a classic Chinese herbal formula which consists of Astragali mongholici Radix and Angelica sinensis Radix (ASR). For chemical ingredients, HPLC were performed. Results showed compared with single herbs, DBT decoction could promote the dissolution of ingredients such as ferulic acid and calycosin. Furthermore, when ratio of AMR to ASR was 5 to 1, synthetic score was the best. For angiogenesis, normal and injured zebrafish model were applied. Results showed DBT and its ingredients had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…Radix A. sinensis contains angiogenetic modulators such as polysaccharides, ferulic acid, calycosin and calycosin-7-glucoside that may function in angiogenesis and recovery of endothelial dysfunction. 33,34 In our study the functional compound BP derived from Radix A. sinensis exerted antiangiogenetic activity through downregulating VEGF, VEGFR1 and VEGFR2 expression in tumor tissue ( Figure 1E and F). BP is known to suppress human umbilical vein endothelial cell proliferation, migration and capillary tube formation via the activation of p38 and ERK 1/2.…”
Section: Discussionmentioning
confidence: 54%
“…Radix A. sinensis contains angiogenetic modulators such as polysaccharides, ferulic acid, calycosin and calycosin-7-glucoside that may function in angiogenesis and recovery of endothelial dysfunction. 33,34 In our study the functional compound BP derived from Radix A. sinensis exerted antiangiogenetic activity through downregulating VEGF, VEGFR1 and VEGFR2 expression in tumor tissue ( Figure 1E and F). BP is known to suppress human umbilical vein endothelial cell proliferation, migration and capillary tube formation via the activation of p38 and ERK 1/2.…”
Section: Discussionmentioning
confidence: 54%
“…Studies have shown that the five chemical components can be absorbed into the plasma [ 9 ] through small intestine [ 10 ] and are related to vascular remodeling factors. Both ferulic acid and calycosin-7-glucoside could improve endothelium dysfunction in dose dependence [ 11 ]. Formononetin has a suppressive effect on PDGF-BB-stimulated VSMCs proliferation and migration, which occur partly via the inhibition of Akt signaling pathway [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Danggui Buxue Tang (DBT) is a classic Chinese herbal formula which consists of Astragali mongholici Radix and Angelica sinensis Radix (ASR). DBT may enhance angiogenesis and relieve endothelial dysfunction induced by lysophosphatidyl choline ( Lin et al, 2017 ).…”
Section: Chinese Herbal Medicines Targeting Angiogenesis In Ischemic mentioning
confidence: 99%